A new formulation of poly(MAOTIB) nanoparticles as an efficient contrast agent for in vivo X-ray imaging. (15th January 2018) - Wallyn, Justine; Anton, Nicolas; Serra, Christophe A.; Bouquey, Michel; Collot, Mayeul; Anton, Halina; Weickert, Jean-Luc; Messaddeq, Nadia; Vandamme, Thierry F.
Graphical abstract: Abstract: Polymeric nanoparticles (PNPs) are gaining increasing importance as nanocarriers or contrasting material for preclinical diagnosis by micro-CT scanner. Here, we investigated a straightforward approach to produce a biocompatible, radiopaque, and stable polymer-based nanoparticle contrast agent, which was evaluated on mice. To this end, we used a nanoprecipitation dropping technique to obtain PEGylated PNPs from a preformed iodinated homopolymer, poly(MAOTIB), synthesized by radical polymerization of 2-methacryloyloxyethyl(2, 3, 5-triiodobenzoate) monomer (MAOTIB). The process developed allows an accurate control of the nanoparticle properties (mean size can range from 140 nm to 200 nm, tuned according to the formulation parameters) along with unprecedented important X-ray attenuation properties (concentration of iodine around 59 mg I/mL) compatible with a follow-up in vivo study. Routine characterizations such as FTIR, DSC, GPC, TGA, 1 H and 13 C NMR, and finally SEM were accomplished to obtain the main properties of the optimal contrast agent. Owing to excellent colloidal stability against physiological conditions evaluated in the presence of fetal bovine serum, the selected PNPs suspension was administered to mice. Monitoring and quantification by micro-CT showed that iodinated PNPs are endowed strong X-ray attenuation capacity toward blood pool and underwent a rapid and passive accumulation in the liver and spleen. Statement of Significance: The design of X-ray contrast agents for preclinical imaging is still highly challenging. To date, the best contrast agents reported are based on iodinated lipids or inorganic materials such as gold. In literature, several attempts were undertaken to create polymer-based X-ray contrast agents, but their applicability in vivo was limited to their low contrasting properties. Polymer-based contrast agents present the advantages of an easy surface modification for future application in targeting. Herein, we develop a novel approach to design polymer-based nanoparticle X-ray contrast agent (polymerization of a highly iodine-loaded monomer (MAOTIB)), leading to an iodine concentration of 59 mg/mL. We showed their high efficiency in vivo in mice, in terms of providing a strong signal in blood and then accumulating in the liver and spleen.